2009
DOI: 10.1111/j.1600-0609.2009.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

The −509C/T polymorphism of transforming growth factor‐β1 is associated with increased risk for development of chronic idiopathic neutropenia

Abstract: The TGF-beta1 -509C/T polymorphism is associated with increased risk for CIN and contributes to the pathophysiology of the disorder by inducing TGF-beta1 overproduction. This is the first study providing evidence that genetic factors may predispose to CIN and may have a role in the pathophysiology of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…5A. Genotype data of this group of CIN patients have been reported previously [32]. We found that the group of CIN patients with the mutant CT (n ¼ 7) or TT (n ¼ 3) genotype displayed significantly increased levels of TGF-b1 in P2, P4, and P6 MSC culture supernatants (1946 AE 1085, 1195 AE 1024, and 652 AE 277 pg=mL, respectively) compared with patients with the wild-type CC genotype (n ¼ 4) (678 AE 227, 327 AE 79, and 233 AE 51 pg=mL, respectively; P ¼ 0.002, P ¼ 0.002, and P ¼ 0.008, respectively) or the healthy controls (858 AE 273, 422 AE 324, and 266 AE 206 pg=mL, respectively; P ¼ 0.0004, P ¼ 0.0029, and P ¼ 0.0005, respectively).…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…5A. Genotype data of this group of CIN patients have been reported previously [32]. We found that the group of CIN patients with the mutant CT (n ¼ 7) or TT (n ¼ 3) genotype displayed significantly increased levels of TGF-b1 in P2, P4, and P6 MSC culture supernatants (1946 AE 1085, 1195 AE 1024, and 652 AE 277 pg=mL, respectively) compared with patients with the wild-type CC genotype (n ¼ 4) (678 AE 227, 327 AE 79, and 233 AE 51 pg=mL, respectively; P ¼ 0.002, P ¼ 0.002, and P ¼ 0.008, respectively) or the healthy controls (858 AE 273, 422 AE 324, and 266 AE 206 pg=mL, respectively; P ¼ 0.0004, P ¼ 0.0029, and P ¼ 0.0005, respectively).…”
mentioning
confidence: 67%
“…Previous studies have also shown elevated TGF-b1 levels in patient sera and LTBMCs and this cytokine has been critically involved in the pathophysiology of CIN by affecting several parameters of hematopoiesis [4,5,7,32,33]. It has also been proposed that TGF-b1 overproduction in CIN may be genetically determined because CIN patients display at a high frequency the TGF-b1-509C=T polymorphism, which in turn is associated with the elevated cytokine concentration in peripheral blood and LTBMC supernatants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible association between the elevated levels of the above soluble mediators and the genetic predisposition for CIN has been investigated by two different groups. Although the −308G/A polymorphism of the TNF- α gene, especially the TNF2 allele, had been previously shown to contribute to increased serum levels of this cytokine in other disease entities [92, 93], no association was identified between this polymorphism with either the occurrence or the severity of neutropenia in CIN subjects [94, 95]. Likewise, no difference in frequency of the −511C/T IL1B and the +3953C/T IL1B SNP or the variable number tandem repeat (VNTR) in intron 2 of IL-1Ra gene (IL1RN) was detected in CIN patients, [95] although these polymorphisms have been associated with IL1B gene expression and increased IL-1 β production [96, 97].…”
Section: Chronic Idiopathic Neutropeniamentioning
confidence: 99%